Intervention for abdominal aortic artery stenosis with dissected, aneurysmal lesions - Binh, Ho Anh; Duy, Le Van; Thiet, Nguyen The; Tien, Hoang Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Severe abdominal aortic stenosis with dissection and aneurysm is a complex and rare condition. Previously, traditional open abdominal aortic replacement surgery was often used to treat aorta lesions. Endovascular intervention has recently proven to be a treatment method with many advantages as a feasible and safe alternative to open surgery, providing high recanalization effciency, with attractive long-term results, The rate of re-intervention and complications is low, and shorter hospital stay, especially for infrarenal abdominal aortic artery lesion. Many great advances in improving cardiovascular interventional devices over the past decade, endovascular intervention with aortic stent placement in patients with severe abdominal aortic stenosis with aneurysm lesions and complex dissections achieved a high success rate. We respectfully share our treatment experiences in 2 cases of severe complicated abdominal aortic stenosis with aneurysm and dissection that were successfully treated with stent placement.